Pengaruh Pemakaian Limbah Genteng Beton Terhadap Mutu Beton Sedang - Warsiti Warsiti (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2011)
In line with the economical development, there are a lot of old buildings renovation which produces material waste like roof tile.To use the existing roof tile waste, the research on the use of cncrete roof tile waste for concrete mixture was performed considering that concrete roof tele fraction is hard enough. By using part of concrete roof tile fraction in the agregate for concrete mixture, it is expected that it doesn’t affect the quality or pressure strength of produced concrete. This is more economical since the pebble price is more expensive than concrete roof tile price. The aim of the reseach is to find out the percentage of concrete roof tile fraction in the coarse aggregate for concrete mixture so that it doesn’t affect the concrete pressure strenght, seek for the correlation between concrete pressure strenght and the precentage of concrete roof tile fraction in coarse aggregate for concrete mixture, seek for the correlation between concrete pressure strenght and aggregate weathering. In the research, the testing material is in the form of cube 15 x 15 x 15 cm with slump value as the fixed variable mean while the non fixed variable is the precentage of concrete roof tile fraction in the mixture, that is 0, 10, 20, 30, 40, 50 % of is coarse aggregate. From the result of the research, it is obtained that in the 10 % percentage of concrete roof tile fraction, the generated concrete pressure strength doesn’t change or has no influence. The correlation between concrete pressure strength and the percentage of concrete roof tile fraction in the aggregate is y = -1.539 x + 242.6 and the correlation between concrete pressure strength and the aggregate weathering is y = -6.519 x2 + 242.2 x – 2013. With the percentage ot roof tile fraction in the aggregate asmuch as 50 % may affects the decreasing of concrete quality and the concrete pressure strength reaches 29.5%.